2013
DOI: 10.1093/iwc/iws011
|View full text |Cite
|
Sign up to set email alerts
|

Boredom and Distraction in Multiple Unmanned Vehicle Supervisory Control

Abstract: Operators currently controlling Unmanned Aerial Vehicles report significant boredom, and such systems will likely become more automated in the future. Similar problems are found in process control, commercial aviation, and medical settings. To examine the effect of boredom in such settings, a long duration low task load experiment was conducted. Three low task load levels requiring operator input every 10, 20, or 30 minutes were tested in a four-hour study using a multiple unmanned vehicle simulation environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 66 publications
(68 reference statements)
2
50
0
1
Order By: Relevance
“…Yet, on a practical note as the authors concede, 'it seems implausible that the otherwise idle user will be able to stay focused and searching for a possible risk of an accident which might occur on average once every 2 million kilometres or so' (Hevelke and Nida-Rümelin 2015). Research involving unmanned aerial vehicles in the military domain suggests that human boredom degrades both reaction times and the ability to maintain directed attention in oversight tasks (Cummings et al 2013) which corroborate this claim. Taken together, this undermines the prospect for capacity responsibility for the occupant human beings for the harms caused by their autonomous vehicles.…”
Section: Role and Capacity Responsibility; Causal Responsibilitymentioning
confidence: 91%
“…Yet, on a practical note as the authors concede, 'it seems implausible that the otherwise idle user will be able to stay focused and searching for a possible risk of an accident which might occur on average once every 2 million kilometres or so' (Hevelke and Nida-Rümelin 2015). Research involving unmanned aerial vehicles in the military domain suggests that human boredom degrades both reaction times and the ability to maintain directed attention in oversight tasks (Cummings et al 2013) which corroborate this claim. Taken together, this undermines the prospect for capacity responsibility for the occupant human beings for the harms caused by their autonomous vehicles.…”
Section: Role and Capacity Responsibility; Causal Responsibilitymentioning
confidence: 91%
“…Hence, these settings are challenging for the operators who ought to maintain sustained attention to be responsive and efficient at all times in such critical systems [1], [2]. Studies have shown that these task settings induce boredom which leads to divided attention and operators being distracted from the task [3], [4]. More specifically sustained attention is effortful [5] and its failures, which have been termed vigilance decrements, can lead to accidents especially when facing critical and unexpected situations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that human operators cannot supply visual attention to each visual display at the same time, they must periodically shift their visual attention between different information sources. While doing so, human operators might fall prey to a couple of demons distracting them from performing adequate monitoring behavior, such as boredom [4], attentional tunneling [5] or perservation [6].…”
Section: Introductionmentioning
confidence: 99%